(Web) cartography and augmented reality: new ways to use digital technologies in teaching geography - Santos, Ana Maria Ferreira dos (Geosaberes; Vol 9 No 17 (2018): Jan - Apr, 2017)
The use of digital technologies, especially in education, can produce more attractive classes and directly influence the cognitive development and wellbeing in school environment. Electronic equipment connected to the internet has become essential to most of the population. Smartphones, in particular, are nowadays the most popular gadget in the world. In this sense, some possible didactic interventions for teaching were outlined here, especially to geography, using digital and virtual technologies based in the context of WEB 2.0 and WEB 3.0, which can be accessed by these devices. This paper focused on (WEB) cartography, augmented reality (AR), and the (GEO) entertainment, applied to Google Earth, Google Street View, applications for RA and online games.